Nationality diversity in corporate boards and tax avoidance: Evidence from Oman - Badar Alshabibi; Shanmuga Pria; Khaled Hussainey (Administrative Sciences, 2022)
We examine the impact of nationality diversity in corporate boards on tax avoidance by assessing whether foreign directors play monitoring or advisory roles. We use a sample of 1049 firm-year observations from companies listed on the Muscat Stock Exchange between 2009 and 2019. We find that board nationality and audit committee nationality are associated with lower effective tax rates, which equated to more tax avoidance (an advisory role). Our findings offer an important implication for policymakers who are interested in determinants of and mechanisms to prevent tax avoidance. The implication is that caution should be exercised when appointing foreign directors to the board of directors in Oman.
Keywords: 350; Oman; nationality diversity; tax avoidance